Frequency of Hypocalcemia in Patients Undergoing Plasmapheresis - Muhammad Ishaq, Arif Rahim Khan, Syed Shahnawaz Hasan, Muhammad Fahad Aziz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the number of patients who experience Hypocalcemia while receiving Plasmapheresis. Study Design: An observational study that is cross-sectional and descriptive. Place and Duration of Study: The research was conducted for one year, from 21th April 2020 to 21th April 2021. Methods: A total of 177 individuals having Plasmapheresis between the ages of 15 and 45 were included in the study. Participants in the study who had recently undergone thyroid or parathyroid surgery, those with renal failure, arrhythmias, and persons who were difficult to comply with, were excluded (1). After that, each patient had a therapeutic plasma exchange, commonly known as Plasmapheresis, performed by skilled medical professionals with comparable levels of expertise. After the process, a venous blood sample was drawn to measure the amount of calcium ionized. Hypocalcemia was either present or not, defined as ionized calcium levels below 4.5 mg/dl. Results: The average age of the eighty-two patients was 38.43 years, and 46.33% were between 36 and 45. Among these 117 patients, 109 of them were men and 68 of them were women, making up 38.42% of the entire population’s patients (61.58%), or a ratio of 1:6:1. Hypocalcemia was found in 18 people with a percentage of 10.17%, whereas the disorder was absent in 159 patients with a percentage of 89.83%. Patients in this group are undergoing Plasmapheresis. Conclusion: Therefore, Plasmapheresis should be used to routinely evaluate serum calcium levels to appropriately manage any cases of Hypocalcemia that may emerge since Hypocalcemia often happens in patients getting Plasmapheresis (10.17% of the time). Keywords: Exchange of plasma, calcium level.